Studi Literatur: Penerapan Model Project Based Learning dalam Pembelajaran IPS di Sekolah Dasar Terhadap Kemampuan Berpikir Kreatif - Nuril Aufah; Diah Fatimatul Makiyah; Vini Nurfauziah Apriani (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
There are still many teachers who apply a teacher-centered learning model, thus triggering the development of students' creative thinking skills to weaken. This approach also does not support efforts to develop students' creative thinking abilities. The objectives of this study are as follows: 1) To find out how to apply the Project Based Learning (PjBL) model in social studies learning in elementary schools to creative thinking skills. 2) To measure the increase in students' creative thinking skills in social studies learning in elementary schools through the Project Based Learning (PjBL) model. The approach in this study is a descriptive approach so that the research procedure produces descriptive data in the form of written words. And using the literature study method as a collection of data and information relevant to the application of the Project Based Learning (PjBL) Model through supporting data sourced from research journals. on the teacher). Students are able to think creatively because student lectures solve problems through giving projects or certain things that often occur in real environments. Students' abilities can be improved through IPS.